Navigating the tides of globalisation and neoliberalism: Possibilities for transformation and democracy in 21st century tertiary education. - Terri Brian (New Zealand Journal of Teachers' Work)
Over the past few decades, the world has experienced a period of major social, economic and political change. Globalisation has placed increasing pressure on our work, families and communities and is continuously transforming the way we live in the 21st century. Internationally, despite renewed and intensified calls for freedom and equality, social and economic inequities continue to increase.  In Aotearoa, New Zealand, these forces have had a large impact on our society, our economy and on our tertiary education system. In an uncertain, 21stcentury world, it is our responsibility as educators to prepare learners for participation in the free market economy. It is also necessary however, to encourage the skills and attributes that will ensure a sustainable and democractic future. To achieve and balance these ideals, requires the creation of humanistic learning environments that promote a culture of self-awareness and critical reflection. This article suggests that, by resisting and reshaping the constraints of the current tertiary education system, it is possible to nurture principles of social equity and justice and to encourage self-determination,  transformation and personal freedom.